2017
DOI: 10.1016/j.transproceed.2017.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Beware Cold Agglutinins in Organ Donors! Ex Vivo Lung Perfusion From an Uncontrolled Donation After Circulatory-Determination-of-Death Donor With a Cold Agglutinin: A Case Report

Abstract: Background We began to recover lungs from uncontrolled Donation after Circulatory Determination of Death donors to assess for transplant suitability by ex-vivo lung perfusion (EVLP) and computed tomography (CT) scan. Our first case had a cold agglutinin with an interesting outcome. Case Report A 60-year-old male collapsed at home and was pronounced dead by Emergency Medical Services personnel. Next-of-kin consented for lung retrieval and the decedent was ventilated and transported. Lungs were flushed with co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Special case was reported that a donor with medical history of hemolytic anemia and known cold agglutinin, whose lungs had a total cold ischemia time of 6.5 h. Established clots and aggregates could be observed from the initiation of EVLP, leading to florid pulmonary edema and cessation of EVLP. Impact of hypothermic preservation on cold agglutinin donors should be consulted before assessment [39].…”
Section: To Find Optimized Markers Of Quality Determinationmentioning
confidence: 99%
“…Special case was reported that a donor with medical history of hemolytic anemia and known cold agglutinin, whose lungs had a total cold ischemia time of 6.5 h. Established clots and aggregates could be observed from the initiation of EVLP, leading to florid pulmonary edema and cessation of EVLP. Impact of hypothermic preservation on cold agglutinin donors should be consulted before assessment [39].…”
Section: To Find Optimized Markers Of Quality Determinationmentioning
confidence: 99%